(untitled) (Research, Society and Development, 2021)
This study evaluated the effect of different concentrations of Brazilian green propolis on the cryopreservation of epididymal sperm from domestic cats. Spermatozoa were collected from cauda epididymis by slicing technique in a TRIS extender, preheated to 37ºC. Then, the sperm were evaluated and divided randomly between the control group (without adding propolis in the extender) and the treatment groups (adding different concentrations of propolis extract in the extender): P1 (0.1 mg/mL), P2 (0.3 mg/mL) e P3 (0.6 mg/mL). Subsequently, sperm were cryopreserved. The evaluated parameters were sperm kinetics by the Computer Assisted Semen Analysis, vigor, viability, membrane functionality, chromatin condensation and morphology. The parameters were measured before and after cryopreservation. Propolis didn’t show toxicity to the sperm in any concentrations, with no changes observed in the motility pattern. There was no significant influence of propolis on motility, vigor, percentage of viable spermatozoa, chromatin quality and other kinetic parameters in the cryopreserved samples. In sperm morphology, it was demonstrated a reduction in the percentage of normal cells in P1 and P2 groups in relation to the fresh sample, control and P3 group. In addition, an interesting effect from the propolis groups was observed on possible growth inhibition of microorganisms in the contaminated samples. Propolis didn’t provide superiority to the sperm parameters evaluated after thawing, except for the values of plasma membrane functionality, which were better. The propolis is an interesting component to be incorporated in the cryoprotectant medium due to its non-toxicity and the potential inhibition of microbial growth.